Phyto Chemical and Anthelmintic Evaluation of Corm of Amorphophallus Campanulatus - R. RAMALINGAM; K. HIMA BINDU; B. BINDU MADHAVI; A. RAVINDER NATH; DAVID BANJI (International Journal of Pharma and Bio Sciences, 2010)
The present study deals with phytochemical and anthelmintic evaluation of corm of Amorphophallus campanulatus. This evaluation revealed the presence of many phytochemical constituents. Corm was extracted with petroleum ether, chloroform and methanol. Crude tannins were isolated from methanol extract. All extracts and crude tannins were evaluated for anthelmintic activity. Chloroform, methanol extracts and crude tannins showed very good anthelmintic activity. Paralysis and death times of crude tannins were very close to the standard drug Albendazole.